PENINGKATAN KESEDIAAN DAN PENGETAHUAN MENJADI RELAWAN RJP MELALUI PERMAINAN PUZLE GAMBAR DI SDN KEDUNGPEDARINGAN 1 KEPANJEN - Hardiyanto Hardiyanto; Frastiqa Fahrany (STIKES Karya Husada Kediri, 2019)
Introduction: The occurrence of cardiac arrest outside the hospital is still an occurrence with frequent and even increasing frequency. While CPR volunteer assistance has been widely reported at low rates in various parts of the world (Abella, 2008). This requires the existence of other recommended methods and methods so that the level of RJP Volunteers' availability and Knowledge becomes more numerous. Teaching to an early age is recommended because the earlier they get to know the RJP management, the better their knowledge going forward. Children are fast and easy learners to be motivated. This then encourages researchers to examine alternative methods that can be used to increase the knowledge and number of CPR volunteers. Objective: The purpose of this study was to determine the benefits of using puzzle games to increase knowledge and willingness to become an RJP volunteer in Kedungpedaringan 1 Kepanjen elementary school students. Method: Quasy experimental research method. The sample used by 65 people by simple random sampling will be divided into 3 groups. Group 1 uses standard teaching techniques (SAP), Group 2 uses Puzzle games and group 3 uses a combination of SAP and Puzzle games. Results: There was a significant effect (p <0.01) between learning using SAP / Modules and Puzzle Games on the level of knowledge and the level of willingness of respondents before and after treatment. Responded stated that they prefer learning using Puzle game. Discussion: Puzle game is a form of educational game where its function is not only as a means of play but also a form of education for students. The function of the game is to create a pleasant atmosphere for students. With a pleasant atmosphere, students can receive and understand information conveyed more easily